LEO-PNT Feasibility Aspects: Satellite Navigation Payload Size, Weight, and Power Analysis - Mayank; Prol, F. S.; Lundén, V.; Saleem, Z.; Foreman-Campins, Guillem; Sharma, S.; Lohan, E. S.; Bhuiyan, M. Z. H.; Kaasalainen, S.; Kuusniemi, H.; Praks, J. (IEEE, 2025)
Low Earth Orbit (LEO) satellites are expected to improve the robustness and reliability of critical Positioning, Navigation, and Timing (PNT) services by increasing both the efficiency and diversity of Global Navigation Satellite Systems (GNSS). However, the feasibility of LEO-PNT services remains uncertain primarily due to the large number of required satellites. The deployment of a LEO-PNT system therefore depends on the feasibility of deploying many LEO satellites with characteristics strongly dependent on the performance requirements of both the payload and the platform. This work addresses the feasibility uncertainty by modeling two potential LEO-PNT payloads and satellite platform designs with different size, weight, and power (SWaP) requirements. Based on simulations and components currently available in the space market, a holistic modeling for the performance of low- and high-SWaP payload designs is evaluated with a focus on clock stability and signal quality. Additionally, the design process includes an assessment of a custom navigation antenna to ensure that the antenna can meet its stringent size and performance constraints. The feasibility of the proposed LEO-PNT constellations is evaluated based on satellite link, power, and mass budgets, as well as antenna performance. In addition, the cost of both the low- and high-SWaP satellites is estimated. This work shows that LEO-PNT payload and constellations are feasible with the technology commercially available today, and they could offer significantly stronger PNT signals compared to traditional GNSS services. The work also benchmarks the proposed payloads against commercial projects in terms of SWaP, timing and positioning accuracy. These results can assist future LEO-PNT simulations to utilize detailed information of payload components and take LEO-PNT services a step closer to realization.
Keywords: atomic clocks; Constellation; Costs; feasibility study; Global navigation satellite system; LEO-PNT; low Earth orbit satellites; Navigation; orbits; Payloads; Satellite broadcasting; satellite navigation systems; Satellites; synchronization; Information Technology tech; Tietotekniikka tekn; Information Technology tech; Tietotekniikka tekn